Combined analysis of differentially expressed lncRNAs and miRNAs in liver tissues of high-fat fed rabbits by transcriptome sequencing - Wang, Jie; Wang, Meigui; Shao, Jiahao; Liu, Zheliang; Fu, Chong; Chen, Guanhe; Zhao, Kaisen; Li, Hong; Sun, Wenqiang; Jia, Xianbo; Chen, Shiyi; Lai, Songjia (Frontiers in Genetics, 2022)
High-fat diet could lead to a series of metabolic diseases, including obesity, and its mechanism is not clear. In this study, the rabbit individuals were fed with high-fat diet, the liver tissues were collected, high-throughput sequencing technology was used to reveal the expression of lncRNA and miRNA difference, and the molecular regulation mechanism of lncRNA-miRNA. A total of 24,615 DE lncRNAs and 52 DE miRNAs were identified, including 15 novel discovered DE miRNAs (5 upregulated and 10 downregulated). Furthermore, five miRNAs and three mRNAs were verified by qRT-PCR, and the results showed that the expression of the DE miRNAs and DE lncRNAs in the two groups was consistent with our sequencing results. GO and KEGG analyzed 7,57,139 target genes respectively, enriching the pathways related to lipid metabolism, including mucin O-glycan biosynthesis pathway, insulin resistance and glucagon signaling pathway. Moreover, 65 targeting relationships were obtained. Among them, LOC103348122/miR-450a-5p, LOC103350359/miR-450a-3p and LOC103350429/miR-148a-5p were proposed the first time. Significantly, LOC103348122/miR-450a-5p and LOC103350429/miR-148a-5p were related to lipid metabolism in the liver. This study is of great significance to the CeRNA regulatory network related to lipid metabolism in the liver of rabbits, and provides a basis for understanding hepatic steatosis in rabbits.